Crack propagation in fracture mechanical graded structures (Fracture and Structural Integrity, 2015)
The focus of manufacturing is more and more on innovative and application-oriented productsconsidering lightweight construction. Hence, especially functional graded materials come to the fore. Due to theapplication-matched functional material gradation different local demands such as absorbability, abrasion andfatigue of structures are met. However, the material gradation can also have a remarkable influence on the crackpropagation behavior. Therefore, this paper examines how the crack propagation behavior changes when acrack grows through regions which are characterized by different fracture mechanical material properties (e.g.different threshold values ?KI,th, different fracture toughness ?KIC). In particular, the emphasis of this paper ison the beginning of stable crack propagation, the crack velocity, the crack propagation direction as well as onthe occurrence of unstable crack growth under static as well as cyclic loading. In this context, the developedTSSR-concept is presented which allows the prediction of crack propagation in fracture mechanical gradedstructures considering the loading situation (Mode I, Mode II and plane Mixed Mode) and the materialgradation. In addition, results of experimental investigations for a mode I loading situation and numericalsimulations of crack growth in such graded structures confirm the theoretical findings and clarify the influenceof the material gradation on the crack propagation behavior.KEYWORDS. Functional fracture mechanical gradation; Crack propagation direction; TSSR-concept;Experimental investigations; Numerical simulations.
Keywords: Functional fracture mechanical gradation